Characterization and preclinical evaluation of a protease activated receptor 2 (PAR2) monoclonal antibody as a preventive therapy for migraine. (December 2020) - Kopruszinski, Caroline M; Thornton, Peter; Arnold, Joanne; Newton, Philip; Lowne, David; Navratilova, Edita; Swiokla, Juliana; Dodick, David W; Dobson, Claire; Gurrell, Ian; Chessell, Iain Patrick; Porreca, Frank
Aim: Migraine pain is thought to result from activation of meningeal nociceptors that might involve dural mast cell degranulation and release of proteases and pronociceptive mediators. Tryptase, the most abundant dural mast cell protease, has been demonstrated to stimulate dural mast cells, as well as trigeminal nociceptors by activating the protease activated receptor 2. Mast cell or neuronal protease activated receptors 2 may therefore represent a novel target for migraine treatment. In this study, we characterized and evaluated a novel protease activated receptor 2 monoclonal antibody as a preventive anti-migraine pain therapy in preclinical models. Methods: Flow cytometry, immunocytochemistry, calcium imaging, Homogeneous Time Resolved Technology (HTRF) epitope competition assay and serum pharmacokinetic (PK) assay in rats were performed to confirm the activity, specificity and in vivo stability of PAR650097, a novel anti- protease activated receptor 2 monoclonal antibody. In vivo assessment was performed in female C57BL/6J mice by evaluation of PAR650097 in preventing cutaneous allodynia elicited by (a) supradural injection of the protease activated receptor 2 agonist, Ser-Leu-Ile-Gly-Arg-Leu-amide trifluoroacetate (SLIGRL), or calcitonin gene-related (CGRP) peptide, and (b) induction of latent sensitization by priming with three daily episodes of restraint stress followed by challenge with a subthreshold inhalational exposure to umbellulone (UMB), a transient receptor potential ankyrin 1 (TRPA1) agonist. PAR650097 was administered as a pretreatment prior to the first restraint stress, umbellulone exposure, SLIGRL or calcitonin gene-related peptide injection. Additionally, fremanezumab, a calcitonin gene-related peptide antibody was administered as pre-treatment prior to supradural administration of calcitonin gene-related peptide or SLIGRL. Results: In vitro, PAR650097 demonstrated rapid interaction with protease activated receptor 2, enabling it to fully inhibit protease-induced protease activated receptor 2 activation, in human and mouse cells, with high potency. Furthermore, PAR650097 was highly selective for protease activated receptor 2, demonstrating no affinity for protease activated receptor 1 protein and no functional effect on the activation of cellular protease activated receptor 1 with thrombin. In addition, PAR650097 had an acceptable PK profile, compatible with testing the effects of selective protease activated receptor 2 inhibition in vivo . In vivo, PAR650097 blocked cutaneous allodynia induced by either supradural SLIGRL or calcitonin gene-related peptide. Fremanezumab abolished cutaneous allodynia induced by supradural CGRP, and partially attenuated cutaneous allodynia induced by SLIGRL. Administration of PAR650097, before the first restraint stress episode, did not prevent the acute stress-induced cutaneous allodynia or restraint stress priming revealed by cutaneous allodynia induced by inhalational umbellulone. In contrast, PAR650097 prevented expression of cutaneous allodynia when given before the umbellulone challenge in restraint stress-primed animals. Conclusion: PAR650097 specifically inhibits endogenously expressed protease activated receptor 2 in human and mouse cells with high potency. This antibody has an acceptable PK profile in rodents and effectively blocked SLIGR-induced cutaneous allodynia. PAR650097 additionally prevented cutaneous allodynia induced by supradural calcitonin gene-related peptide, indicating that the protease activated receptor 2 receptor is a downstream consequence of calcitonin gene-related peptide actions. Fremanezumab effectively blocked calcitonin gene-related peptide-induced cutaneous allodynia and only partially reduced cutaneous allodynia induced by a protease activated receptor 2 activator, suggesting both calcitonin gene-related peptide-dependent and -independent mechanisms in promoting migraine pain. While PAR650097 did not prevent stress-induced cutaneous allodynia or priming, it effectively prevented cutaneous allodynia induced by a TRPA1 agonist in animals with latent sensitization. Activation of protease activated receptor 2, therefore, contributes to both calcitonin gene-related peptide-dependent and -independent mechanisms in promoting migraine-like pain. Therapeutic targeting of protease activated receptor 2 receptors may represent an anti-migraine pain strategy with a potentially broad efficacy profile.